Fabrication of Nano-petals Zn0.97Cu0.03O Thin Film and Application in Methane Sensing - Anchal B.B.N.; Singh P.; Pyare R. (My University, 2025)
This paper presents the fabrication of nano-petals Zn0.97Cu0.03O thin film using electro-spin technique and sensing of methane. Doping of 3% Cu into ZnO was carried out by chemical route and spin coated thin film was grown on a glass substrate. Analysis of XRD, SEM, EDX and AFM characterizations were performed for surface morophology and grain sizes of nano-petals. Study of sensitivity for 1000, 1200 and 1400 ppm methane as better sensing at low operating temperature 125 °C. © 2020, Springer Nature Singapore Pte Ltd.